Desenvolvimento de método para determinação de resíduos de antiparasitários em leite bovino empregando LLE-LTP E LC-MS/MS - Ribeiro, Lucila Cendon (2016)
Milk is one of the most consumed fresh food, considered a nutritionally complete product. Veterinary drugs are used in order to increase productivity. However, improper use of these products may result in the presence of residues in milk. This study aims to develop a method for determination of antiparasitic residues in bovine milk using fast liquid-liquid low temperature partitioning (LLE-LTP) method and liquid chromatographic coupled to tandem mass spectrometry (LC-MS/MS). Different classes were studied for antiparasitic, such as macrocyclic lactones, pyrethroids, benzimidazoles, organophosphates, carbamates, among others. The spikes were held comprising the Maximum Residue Limits (MRLs) of each compound at levels 1- 200 ug L-1. For validation step was adopted the following parameters: selectivity, linear range, matrix effect, limits of detection (LOD) and quantitation (LOQ), decision limit (CCα) and detection capability (CCβ), precision, accuracy. The method was considered valid to 55 antiparasitic and presented LOD from 0.03 to 6.0 μg L-1 and LOQ from 1 to 20 ug L-1. Recoveries were between 70 and 120% with RSD ≤ 20%, that were considered acceptable. The proposed method was applied to 15 real samples where all samples presented residues of at least one antiparasitic. Of these, two samples contained cyhalothrin and nicarbazin residues above the MRL. However, the method was efficient in determining antiparasitic residues in bovine milk using LLE-LTP and LCMS/ MS, showing good sensitivity and selectivity.